Achados clínicos laboratoriais como auxiliares no diagnóstico de histoplasmose disseminada em pacientes febris com AIDS de hospital de referência do Ceará - Ramos, Isadora Cavalcanti (2008)
Disseminated histoplasmosis (DH) is a severe disease that delay in diagnosis and specific treatment is associated with a high mortality. Since the AIDS epidemic, cases of DH are frequently diagnosed in patients with HIV from Fortaleza, a city in Northeastern Brazil. A cross sectional study was conducted on AIDS patients with symptoms suggestive of HD at hospital admission to correlate clinics and laboratory findings with the definitive diagnostic of this mycose, in a reference hospital from January 2006 to January 2007. There were identified 48 DH from 136 subjects. Patients with DH had more temperature higher than 38,5°C, splenomegaly, hepatomegaly, multiple papular skin lesions and sibilant respiratory sound (p<0.05). The more frequent manifestations in other diseases were pleuritic pain and arthralgia (p<0.05). High levels of lactate dhydrogenase (LDH), aspartate aminotransferase (AST) and amylase as well as lower levels of hemoglobin (≤10 g/dl) and CD4 (≤ 75 cel/mm3) were more frequent in DH (p<0.05). Multivariate analysis showed that temperature higher than 38,5°C (adjusted OR, 5.9; p=0.007; 95% CI= 1,62-21,77), LDH level ≥ 5 times normal (adjusted OR, 4.3; p=0.007; 95% CI= 1,49-12,55), CD4 ≤ 75 cel/mm3 (adjusted OR, 4.9; p=0.004; 95% CI= 1,64-14,88), hepatomegaly (adjusted OR, 3.4, p=0.01; 95% CI= 1,33-8,55) and multiple papular skin lesions (adjusted OR, 5.8; p=0.01; 95% CI= 1,50-22,68) were independently associated like the diagnosis of HD. Pleuritic pain was associated negatively with HD diagnosis (adjusted OR 0.2, p=0.02; 95% CI= 0,06-0,78). Suspected DH patients without hepatomegaly and temperature < 38,5°C have negative predictive value for DH of 100%. Patients without elevated LDH have negative predictive value for HD of 74,3%. We can eliminate most DH in patients without hepatomegaly, temperature < 38,5°C and normal LDH. This study helped diagnosis of HD among suspected patients.